The effects of energy management practices on ecological performance: mediating role of renewable energy supply chain - Mohammed Hammam, Mohammed Almadani (2022)
The adoption of energy management practices to achieve ecological performance remains a top priority for manufacturing firms. There are few studies that focus on ecological performance from a management standpoint, and this research area needs to be prioritized. The ecological sustainability of manufacturing firm has become a contemporary concern around the world. The prosperity of Malaysia's manufacturing industry is critically dependent on the efficiency of resource utilization, economic visibility, and environment protection. The study's goal is to develop and test an integrative framework linking Malaysia’ government incentives and manufacturing firms' energy management practices (EMPs) to ecological performance via the mediating role of the renewable energy supply chain, based on the perspective of resource-based view and natural resource-based view theory. The descriptive statistics was performed using SPSS software. Smart PLS version 3.0 was employed to test the hypothesis and dependability and validity of constructs. According to the findings of a survey of 129 Malaysian manufacturing respondents, government incentives have a significant impact on energy management practices. Only energy auditing has an impact on the renewable energy supply chain among energy management practices. It was also discovered that the renewable energy supply chain mediates the relationship between EMPs and ecological performance, which is bolstered by energy auditing. Furthermore, the renewable energy supply chain had an impact on the ecological performance. More research is needed to determine how renewable energy supply chains can assist manufacturers in improving their ecological performance. Finally, Malaysian manufacturing enterprises should improve their efforts toward sustainability to remain relevant in future markets. The study contributes to the identification of new research directions for monetizing ecological concepts such as energy efficiency and government incentives leading to higher ecological performance of manufacturing firms. Policymakers are advised to align energy policy with environment policy to encourage renewable energy adoption, environment protection, energy security and long-term economic growth.